A novel dynamic stress analysis in bimaterial composite with defect using ultrasonic wave propagation. (15th November 2015) - Li, Ran; Natsuki, Toshiaki; Ni, Qing-Qing
Abstract: A new method to evaluate dynamic stress distribution of composite materials is presented using ultrasonic wave propagation analysis. In this method, a two-dimensional bimaterial composite with elliptical defect is modeled by using finite element analysis software. Based on elastic wave propagation analysis, the deformation and dynamic stress fields against different material properties are simulated. As the material properties change, the stress distribution at free edge and interface also change causing different stress wave propagation behavior. By investigating the dynamic stress distribution, the interaction of stress singularities at free edge, mode conversion at interface and wave propagation is clarified. The simulation results show that ultrasonic wave propagation analysis is a convenient and effective way to evaluate the correlation between material properties, stress singularities and dynamic internal stress distribution in composite materials.